GENDER MAINSTREAMING IN SERBIA: DOES IT WORK FOR WOMEN? - Dokmanović, Mirjana (Politeia, 2025)
In recent years, the Republic of Serbia has achieved an evident progress in developing the gender equality legal, policy, and institutional framework. However, the economic, social, and political position of women, particularly of those belonging to vulnerable groups, is still worse than that of men, although women and men are equal by law with respect to rights. The purpose of the article is to contribute to research on the efficiency of gender mainstreaming as a strategy for eliminating the structurally unequal power relations between women and men. The article makes two arguments. First, the evident progress that Serbia made in engendering strategies and legislation has not contributed to a transformative change regarding the subordinated position of women. Second, the gaps between reality and rhetoric are particularly prominent at times of crisis, such as during the COVID-19 pandemic, in which gender issues are not considered important.
Keywords: Gender mainstreaming; public policies; vulnerable groups; COVID-19; gender studies